Efektivitas Pembelajaran Daring Melalui Whatsapp terhadap Minat dan Hasil Belajar Biologi - Irwandi Irwandi; Lusiana Lusiana; Merri Sri Hartati; Nopriyeni Nopriyeni (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effect of online learning through WhatsApp on students' interest and learning outcomes in Biology at SMA Negeri 1 Bengkulu City. The method used in this research is a pre-experiment with a one-group pre-test-post-test design. The research sample was students of class XI IPA 4 SMA Negeri 1 Bengkulu City, totaling 29 students. The results showed an effect before and after being given treatment using online learning via WhatsApp on the interests and learning outcomes of students at SMA Negeri 1 Bengkulu City. In conclusion, WhatsApp is effectively used as a medium in the online Biology teaching and learning process. Keywords: Learning Outcomes, Interests, Online Learning, WhatsApp